Sex and weight category differences in the temporal combat structure of judokas with visual impairment - Gutierrez-Santiago, A.; Gutierrez-Santiago, J. A.; Prieto-Lage, I. (International Journal of Performance Analysis in Sport, 2022)
The study of the temporal judo combat structure of athletes with visual impairment (VI) needs further research. The objectives of the study were to determine the temporal structure of combat of judo in men and women with VI and establish differences between sexes, within their respective weight categories and between the different minutes of combat. The sample was formed by all the judokas with VI who participated in the 2018 IBSA Judo World Championship (172 men and 95 women). Through observational methodology, we analysed all the combats (n = 365). In order to obtain the results, we used different analytical techniques: descriptive, one-way ANOVA, t-test to show independents, chi-square, effect size and T-Patterns analysis. The level of significance was ? = .05. The results define a temporal structure by sex and by weight category that allows the judo professionals to plan precise and adequate trainings for the athletes. We conclude that there are differences in the temporal structure of judo combat within the men and women with VI, within their respective weight categories and within the different minutes of combat. The temporal structure of combat has changed more markedly in women and unevenly in the different weight categories for both sexes.